Two Aspects of Hindu Social Life and Thought, as Reflected in the Works of Tulsidas - Chandra, Savitri (Journal of the economic and social history of the Orient, 1976)
Abstract Tulsi (d. 1623) lived and composed his works 1) in an age in which society and politics had acquired a certain measure of stability after a long period of flux and uncertainty. During the preceding period, a number of saints and thinkers had denounced the institution of caste. Nevertheless, caste still had a considerable hold on the masses, and was considered a vital element of Hindu society by the orthodox. Tulsi attempted to synthesize the prevailing ideas in a framework which would, while rejecting the worst iniquities of the caste system, be acceptable to the powerfully entrenched orthodox elements in Hindu society. This task was not an easy one and, in attempting it, Tulsi sometimes takes up contradictory positions.